VALIDASl SPESIFlKASI CAMPURAN BIODIESEL-SOLAR HASIL PENGUKURAN DENGAN METODA PERHITUNGAN SEDERHANA - Soni S. Wirawan; Armansyah H. Tambunan; Martin Djamin; Hiroshi Nabetani (PERTETA, 2007)
ABSTRACT Biodiesel is a fuel derived from vegetable oil or animal fats that can be used as an additive to or entirely replace conventional petroleum diesel fuel. In most cases, biodiesel is mixed with conventional diesel because of the higher cost of biodiesel, product availability and engine compatibility issues. In Indonesia, the decree No. 3675K/24/DJM/2006 regarding the quality and specification of diesel oil type Solsr 48 and Solar 51 has been issued this decree regulates the use of FAME (fatty acid methyl ester) up to the maximum of 10 percent of the volume of automotive diesel fuel with which it is to be blended. The cost to measure the properlles of fuel is expensive and time consuming, therefore it is important to develop a simple method to predict those blending properties. This paper presents the development of a simple calculation method for the validation of blend palm biodiesel-mineral diesel specification (density, viscosity, cetane number and lubricity) which has been measured in the author's previous study The result shows that the lubricity and viscosity shows a higher average error value (difference value between calculation and measurement result) of 1.66% and 1.35%, whereas density and cetane number shows lower average error values of 0.06 and 0.6%. The average error value less than 2% is still acceptable. Keywords: Biodiesel, blend, fuel properties, density. cetane, viscosity, lubricity Diterima; 20 Agustus 2007; Disetujui: 31 Agustus 2007